Peningkatan Kuat Tekan Bebas (UCS) Tanah Lempung (CH) Terhadap Penambahan Limbah Bafa (Bottom Ash &Fly Ash) Dan Semen - Lala Monang Robert Christian Zega Zega; Syawal Satibi; Soewignjo Agus Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The research aims to increase the compressive strength of soils based on increasing the value of UCS testing. This study uses clay with high plasticity as research objects. Thisis done because the soil type is known to have problems in building construction. The method used is a UCS sample without a marinade which has been compiled accordingto calculations. The mixed samples that have been made are varied based on curing days which are 0 days, 7 days and 28 days with a variation of the cement mixture of 3%and 5% and a mixture of BAFA waste of 4%, 8%, 12% and 16%. a sample naming method is also provided so that it is easy to summarize the results of each test based onplanned variations. Based on the test results that the addition of cement and BAFA increase the free compressive strength (Cu) and compressive strength (qu) of high plasticity soft soil. This increase in value results in an increase in the value of E50 orincrease the stiffness of the UCS sample. The highest increase in UCS occurred in soil with 5% cement and BAFA 16% with 28 days Curing. The increase in qu in the UCS sample was greatest in the variation of sample A-S5-B16-C28 with a value of 94.79 kPa, this increase was 76.57% when compared with the value of qu A which was 22.04kPa. Based on microscopic testing of UCS samples, it can be seen that the higher the level of BAFA and Cement, changes in the structure of the sample look coarser and paler.Keywords : UCS, Microscopic, Cement, Bottom Ash, Fly Ash.